Gamma-Irradiated Non-Capsule Group B Streptococcus Promotes T-Cell Dependent Immunity and Provides a Cross-Protective Reaction - Yong Zhi; Fengjia Chen; Guangxu Cao; Fang Li (MDPI AG, 2023)
Group B Streptococcus (GBS) is a Gram-positive bacterium commonly found in the genitourinary tract and is also a leading cause of neonatal sepsis and pneumonia. Despite the current antibiotic prophylaxis (IAP), the disease burdens of late-onset disease in newborns and non-pregnant adult infections are increasing. Recently, inactivation of the pathogens via gamma radiation has been proven to eliminate their replication ability but cause less damage to the antigenicity of the key epitopes. In this study, the non-capsule GBS strain was inactivated via radiation (Rad-GBS) or formalin (Che-GBS), and we further determined its immunogenicity and protective efficacy as vaccines. Notably, Rad-GBS was more immunogenic and gave rise to higher expression of costimulatory molecules in BMDCs in comparison with Che-GBS. Flow cytometric analysis revealed that Rad-GBS induced a stronger CD4+ IFN-γ+ and CD4+IL-17A+ population in mice. The protective efficacy was measured through challenge with the highly virulent strain CNCTC 10/84, and the adoptive transfer results further showed that the protective role is reversed by functionally neutralizing antibodies and T cells. Finally, cross-protection against challenges with prevalent serotypes of GBS was induced by Rad-GBS. The higher opsonophagocytic killing activity of sera against multiple serotypes was determined in sera from mice immunized with Rad-GBS. Overall, our results showed that the inactivated whole-cell encapsulated GBS could be an alternative strategy for universal vaccine development against invasive GBS infections.